Analysis of the effects of ha-330 hemo adsorption column application on mortality andmorbidity of adult patients with sepsis in general intensive care unit - UYSAL, HARUN; Koç S.; Dokur M.; Uysal H. (My University, 2022)
Sepsis is a leading cause of mortality and morbidity in critical care units. The objective of this study is to evaluate if using the HA-330 Sepsis Adsorption Column in the intensive care unit reduces mortality and morbidity in patients with sepsis. This study was designed as a retrospective study evaluating demographic and laboratory parameters in the General Intensive Care Unit. The study involved 200 sepsis patients who were followed in the critical care unit between June 2019- December 2020 and were treated with the HA-330 Sepsis Adsorption Column. The length of hemoperfusion in patients who died was statistically significantly longer than in patients who recovered. The mean lactate and the hemoperfusion time/day value had a weak but significant negative correlation. In the recovery and death observations, the improvements in repeated C-reactive protein and Procalcitonin measurements were statistically significantly different. The differences in repeated pH and lactate measurements in the recovery and mortality observations were statistically identical, according to the observations. Sepsis-related deaths are a severe issue in critical care units. HA-330 Sepsis Adsorption Column, it can be thought that it can be an inexpensive, useful, and effective method that can be used in the prognosis of the patients. In antibiotic-resistant sepsis, hemoperfusion may be recommended.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)